2015
DOI: 10.1021/acs.jafc.5b00846
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Biochar Surface Oxidation during Composting?

Abstract: Biochar composting experiments were performed to determine whether composting is a suitable method to accelerate biochar surface oxidation for increasing its reactivity. To assess the results, surface properties of Terra Preta (Brazil) and ancient charcoal pit (Northern Italy) biochars were additionally investigated. Calculation of O/C ratios by energy-dispersive X-ray spectroscopy demonstrated the anticipated increasing values from fresh biochars (0.13) to composted biochars (0.40), and finally charcoal pit b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 29 publications
3
44
0
Order By: Relevance
“…These values were found to be as follows: 83.06% C, 7.4% H, 0.48% N, 6.03% ash, and 0.26% O. Surface area was determined using a Quantachrome Autosorb‐1‐MP instrument as described in Zhou et al (2015). Briefly, sample material was weighed and placed in a 12‐mm sample cell, outgassed, reweighed, and dosed with known quantities of ultrahigh purity N 2 gas.…”
Section: Methodsmentioning
confidence: 99%
“…These values were found to be as follows: 83.06% C, 7.4% H, 0.48% N, 6.03% ash, and 0.26% O. Surface area was determined using a Quantachrome Autosorb‐1‐MP instrument as described in Zhou et al (2015). Briefly, sample material was weighed and placed in a 12‐mm sample cell, outgassed, reweighed, and dosed with known quantities of ultrahigh purity N 2 gas.…”
Section: Methodsmentioning
confidence: 99%
“…The binding effect of these functional groups with hydrogen ion in soil led to the increase in soil pH. It has been found that compost could promote the formation of oxygen-containing functional groups in biochar surface on account of the complicated interaction of oxidation and sorption (Khan et al, 2016;Wiedner et al, 2015). Therefore, the specific change of soil pH resulting from the proportion changes between biochar and compost in this study might be explained as follow: when the biochar percentage is low, the interaction between biochar and compost is weak and less due to low biochar amount and high compost content and the weak acidity of compost (pH ¼ 6.23) ( Table 2), so the soil pH increases slightly; as the biochar percentage rises gradually and reaches to 20% and 40%, the higher soil pH is obtained, which might be attribute to the fact that 20% and 40% biochar addition could effectively promote the interaction between biochar and compost.…”
Section: Effects Of Amendments On Soil Chemical Characteristicsmentioning
confidence: 99%
“…The biochar was produced from green cuttings in a Pyreg™ reactor at around 650°C (Doerth, Germany, http://www.pyreg.de) ( Wiedner et al., , ). Biochar additions varied, with treatments receiving a single application of biochar in 2012 at a rate of 40 Mg ha −1 (B40) or 1 Mg ha −1 for three consecutive years, resulting in a total application of 3 Mg ha −1 (B3) over the duration of the experiment.…”
Section: Methodsmentioning
confidence: 99%